Acoustic and Gamma-ray attenuation studies of K2O-PbO-SiO2 glass system (Baghdad Science Journal, 2024)
Acoustic and gamma ray investigations of K2O-PbO-SiO2 glass system have been carried out to explore their structure and gamma-ray attenuation properties. Acoustic studies are carried out to study the effect of concentration of lead oxide on the connectivity of the glass structure. Elastic properties are estimated for getting information regarding the dimensionality and rigidity of the network. Gamma -ray mass attenuation coefficient is calculated theoretically as well as experimentally at 511KeV, 662KeV &1274.0KeV photon energy values. Experimental values of Gamma-ray attenuation coefficients are compared to theoretical values computed using NIST-XCOM software. Results of half value layer (HVL) for prepared glasses are compared with ferrite concrete to explore the scope of lead-based glasses as suitable candidates for radiation shielding materials.